ChemInform Abstract: Efficient Conversion of Acids and Esters to Amides and Transamidation of Primary Amides Using OSU‐6. Issue 11 (February 2016) - Nammalwar, Baskar; Muddala, Nagendra Prasad; Watts, Field M.; Bunce, Richard A.
Abstract: The metal‐ and solvent‐free simple one‐pot protocol is efficiently applied to the amidation or transamidation, respectively, of aromatic carboxylic acids, aromatic ortho‐diacids, aromatic esters, aromatic primary amides, phthalimides as well as acetamide and formamide using aromatic, hetaromatic, or aliphatic primary amines as well as morpholine and hydrazine.